2016
DOI: 10.1159/000444444
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Hepatic Portal Venous Gas after Abdominal Surgery

Abstract: Hepatic portal venous gas (HPVG) is induced by various abdominal diseases. Since HPVG is accompanied by bowel ischemia, intestinal infection and hypovolemia, various modes of critical management are needed to treat the underlying conditions. HPVG associated with abdominal complications after surgery has rarely been reported. We present 4 patients with HPVG after abdominal surgery: 2 of the 4 patients died of multiple organ failure, and the other 2 recovered with solely conservative therapy. Although postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Case reports of on HPVG associated to benign etiologies have been increasing since 1980 with the increased use of more sensitive diagnostic imaging techniques (ultrasonography and CT). The high mortality rate lead to consider HPVG an indication of mandatory explorative laparotomy throughout the last fifty years [8], [9], [11]. The latter increase incidence of benign conditions HPVG correlated suggest to change the common invasive therapeutic approach to lesser invasive treatment [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports of on HPVG associated to benign etiologies have been increasing since 1980 with the increased use of more sensitive diagnostic imaging techniques (ultrasonography and CT). The high mortality rate lead to consider HPVG an indication of mandatory explorative laparotomy throughout the last fifty years [8], [9], [11]. The latter increase incidence of benign conditions HPVG correlated suggest to change the common invasive therapeutic approach to lesser invasive treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…There is a scant literature on HPVG induced by postoperative complication after surgery. Although is a severe and life threatening condition, early detection and sistemic treatment lead to a better patient outcome as in our experience [6], [7], [8], [9], [10], [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is often related to significant underlying pathologies such as intestinal ischemia, sepsis, inflammatory bowel diseases, bowel obstruction, diverticulitis, appendicitis, and trauma. Rarely, hepatic portal venous gas after an upper gastrointestinal endoscopy and dilation for benign esophageal strictures with EoE has also been reported in few studies [124, 125].…”
Section: Complicationsmentioning
confidence: 99%
“…Furthermore, in our literature review, we reported a paper that presented a case of HPVG with anastomosis leakage [3]. Other papers we reported presented cases of HPVG due to surgical complications, while not specifying which types [4][5][6][7]. We write this letter to specify that the HPVG condition could be associated with anastomotic leakage and the management of this surgical complication should also solve the portal venous gas problem.…”
Section: To the Editormentioning
confidence: 99%
“…In our case, “a computed tomography scan showed little perianastomotic collections with air-fluid levels and massive hepatic portal venous gas.” Furthermore, in our literature review, we reported a paper that presented a case of HPVG with anastomosis leakage [ 3 ]. Other papers we reported presented cases of HPVG due to surgical complications, while not specifying which types [ 4 - 7 ].…”
mentioning
confidence: 99%